Outtcome of Fllexiiblle Naiilliing iin Forearm Fracttures iin Chiilldren - Rehman, Hafiz Faiz ur; Amin, Muhammad Suhail; Shah, Mian Qaisar Ali; Labib, Muhammad; Iqbal, Muhammad Nouman; Qureshi, Bilal Ahmed (Pakistan Armed Forces Medical Journal, 2024)
Objective: To look for outcome and analyze the factors influencing outcome of flexible nailing in forearm fractures in childrenmanaged at tertiary care orthopedics unit.Study Design: Case Series.Place and Duration of Study: Orthopedic Department, Combined Military Hospital, Rawalpindi Pakistan, from Jul 2022 toMar2023.Methodology: A prospective case series was conducted on the pediatric patients managed for forearm fractures with flexiblenailing in our orthopedics unit. Outcome was assessed at 10 weeks after the surgical procedure. Poor outcome was defined ifthere was non-union on x-ray, pain on range of motion or skin erosion at site of nailing. Factors like age, gender, poly traumaand anemia at time of presentation were associated with poor outcome in children recruited in this case series.Results A total of 30 children with forearm fractures treated with flexible nails were included in the final analysis. Out of them23(76.6%) were male while 07(23.4%) were females. Mean age of the children recruited in study was 5.83±2.16 years. 20(66.7%)children with forearm fracture treated with flexible nails had good outcome after surgery while 10(33.3%) had poor outcome.Chi-square analysis revealed that poly trauma and presence of anemia at the time of presentation were the factors statisticallysignificant associated with poor outcome (p-value